2008
DOI: 10.1016/j.jmb.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Dynamics of the Wild-type Pseudoknot of Human Telomerase RNA

Abstract: SUMMARY Telomerase is a ribonucleoprotein complex that replicates the 3’ ends of linear chromosomes by successive additions of telomere repeat DNA. The telomerase holoenzyme contains two essential components for catalysis, a telomerase reverse transcriptase (TERT) and telomerase RNA (TER). The TER includes a template for telomere repeat synthesis as well as other domains required for function. We report the solution structure of the wild type minimal conserved human TER pseudoknot (PKWT) refined with an extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
160
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(169 citation statements)
references
References 59 publications
9
160
0
Order By: Relevance
“…Previous NMR studies suggested that an isolated pseudoknot sequence from the human telomerase RNA slowly interconverts between a hairpin state and the pseudoknot conformation on the timescale that is longer than seconds (22,33), whereas mutational analysis of human telomerase supports a static pseudoknot structure (25). In the single-molecule time traces shown here, neither stem A nor stem B were observed to undergo conformational rearrangements in the wild-type pseudoknot during primer extension or enzyme translocation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous NMR studies suggested that an isolated pseudoknot sequence from the human telomerase RNA slowly interconverts between a hairpin state and the pseudoknot conformation on the timescale that is longer than seconds (22,33), whereas mutational analysis of human telomerase supports a static pseudoknot structure (25). In the single-molecule time traces shown here, neither stem A nor stem B were observed to undergo conformational rearrangements in the wild-type pseudoknot during primer extension or enzyme translocation.…”
Section: Discussionmentioning
confidence: 55%
“…Phylogenetic analyses of ciliate (9,17), yeast (18)(19)(20), and vertebrate (21) RNAs suggest that this region may fold into a pseudoknot structure. NMR and single-molecule force studies of the isolated pseudoknot sequence from human show that this sequence can indeed form a pseudoknot structure (22,23). Mutation analyses indicate that disruption of potential base pairs in the motif correlates with telomerase assembly and activity defects in multiple organisms (18,24,25), but in vitro telomerase activity assays give varying results on the functional importance of the motif (12,13,(26)(27)(28).…”
mentioning
confidence: 99%
“…The assignments of preQ 1 and interactions in the binding pocket were identified as described previously (33). Single-bond C-H and N-H RDCs were measured using 2D 1 H-13 C S3CT-HSQC and standard 1 H-15 N HSQC experiments as described previously (70), and are listed in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…TER pseudoknot domain (nt contains the telomeric repeat template [91]. Together with the TER CR4-CR5 domain (nt , the pseudoknot domain is also necessary for the binding of TERT and optimal enzyme processivity [54, 92,93]. The hairpin-hinge-hairpin-ACA (H/ACA) motif of TER at nt 275-451 is critical for its cellular accumulation, 3′ end processing, and intranuclear trafficking [58,94].…”
Section: Telomerase Rna (Ter)mentioning
confidence: 99%